Pseudocapacitance phenomena and applications in biosensing devices - Oliveira, Raphael M.B. [UNESP]; Fernandes, Flávio C.B. [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier, 2019)
The concept of electrochemical capacitance comprises both double-layer grounded capacitive (non-faradaic charging) and pseudocapacitive (faradaic charging) behaviours, as has been recently demonstrated [1–3]. In this paper, we demonstrate that nanostructured compounds possessing electrochemical capacitance can be used to design suitable interfaces for label-free biosensing applications, which, moreover, do not require a redox probe to be added to biological samples before assaying. This is possible when the capacitive transducer layer of the biosensor device is kept within an appropriate length scale (for instance, thicknesses lower than 10 nm) in which mesoscopic electrochemical properties prevail. Hence, we demonstrate how the capacitive signatures of Prussian Blue nanostructured films can be envisioned as transducer signals in biosensor devices in general, going beyond traditional redox monolayers, using aqueous electrolytes. This approach is illustrated using electroactive films made of Prussian Blue nanoparticles and modified with appropriate receptors, which successfully and specifically detected interleukin-6, a small biomarker, with a limit of detection of 5.6 ± 0.3 ng mL −1 . In summary, the application of Prussian Blue pseudocapacitive properties in label-free biosensor devices were demonstrated as a proof-of-concept of how such applications can be engineered.
Keywords: Electrochemical biosensors; Molecular electrochemistry; Nanoscale energy-storage principles; Nanostructures; Pseudocapacitors; Supercapacitors